The physical and chemical properties of the waste water from the Nitrogen Fertilizers Industry Company / Basra - Khor Al-Zubair (Journal of the College of Basic Education, 2022)
The study was conducted to identify the physical and chemical properties of the water drained from the Southern Fertilizer Company, where the temperature, pH, ammonia, urea, chemical oxygen demand, biological oxygen demand, dissolved and suspended solids, nitrates, phosphates, iron, zinc were measured for the period from October 2013 until the end of March 2014 at a sample rate every two weeks. The average results of four plants within the company were approved: raw water, waste water from the cooling tower, water desalination unit, and production units for the purpose of identifying the reasons for the variation in the nature of the discharged water under study. Where the results showed a high concentration of ammonia and urea